Modyfikacje granicy bułgarsko‑greckiej w XX w. (1913‑1947) - Znamierowska-Rakk, Elżbieta (Studia z Dziejów Rosji i Europy Środkowo-Wschodniej, 2011)
Modifications of the Bulgarian – Greek border in the 20th century (1913-1947) The text concentrates on presenting territory and border conflicts between Bulgaria and Greece, which were discussed during three international peace conferences. The first one, held in the summer of 1913 in Bukarest after the second Balkan war that ended in Bulgaria’s defeat, deprived the country of part of Aegean Macedonia. The second conference took place in 1919 in Neuilly, after World War I, and established the border between Bulgaria and Greece. Bulgaria lost West Thracia for the benefit of Greece. Lastly, the third peace conference, held after World War II, in 1946 in Paris, concluded the controversies over the border and territory, giving the two countries quo ante bellum status. As a result, Athens, demands to move the Bulgarian border to the north were dismissed, as well as Sofia’s postulate to regain access to the Aegean Sea. The final outcome of 20 years of battles over a satisfactory border was unfavourable to Bulgarians. The loss of access to ope sea, decided upon after World war I, was sustained after World War II, and has not changed until today. Изменения болгаро‑греческой границы в 20 в (1913‑1947) Статья посвящена описанию болгаро‑греческих территориальных споров во время заседаний трех международных мирных конференций. Решения первой конференции, проходившей летом 1913 г. в Бухаресте после Второй Балканской войны, которая закончилась поражением Болгарии, лишили болгарское государство восточной части Эгейской Македонии (Кавальской Македонии). В свою очередь вторая мирная конференция, установившая линию болгаро‑греческой границы, проходила после Первой мировой войны в 1919 г. в Невилль. На ней было решено, что Болгария лишается Западной Трации в пользу Греции. И в конце концов третья мирная конференция, которая была проведена в Париже в 1946 г после окончания Второй мировой войны, решила болгаро‑греческие территориальные споры, вернув статус‑кво, существующий до войны. В результате отвергнуты были как стремления Афин, касающиеся границы с Болгарией на севере, так и требования Софии, касающиеся получения выхода к Эгейскому морю. Результат двадцатилетней борьбы за установление более выгодной границы с Грецией, к сожалению, оказался для Болгарии неутешительным. Лишение болгарского государства непосредственного выхода к открытому морю, после Первой мировой войны , было сохранено после Второй мировой войны и действует по сегодняшний день.